Redesain Website Ventela untuk Meningkatkan User Experience Pengguna Menggunakan Lean UX - Maidatussohiba, Esa; Novil Maarij, Moh; Wahyu P, Bayu; Dwi Lisnorviona, Maynanda; Ayu Krisna P, Kadek (Rifa'Institute, 2023)
The improvement of user experience (UX) is essential in website development, particularly in the current digital era. Ventela website, an e-commerce platform offering a variety of fashion products, needs enhancements in its UX to meet the increasing needs and expectations of users. In this context, this research aims to redesign the Ventela website with a focus on the Lean UX method to achieve a better user experience. Lean UX is a design approach that emphasizes collaboration among the development team, designers, and users during the design process, while focusing on rapid iterations to ensure the resulting product aligns with user needs. In this research, we identified UX issues on the Ventela website through user analysis, heuristic evaluation, and gathering user feedback. Subsequently, we employed the Lean UX method to redesign the website with a focus on necessary improvements. The results of this research demonstrate a significant transformation of the Ventela website in terms of appearance, functionality, and user experience. The iterative process involving users in every design stage has enabled substantial improvements in navigation, product search, responsiveness, and overall user satisfaction. Consequently, product sales conversion on the Ventela website has significantly increased, proving that the Lean UX approach is an effective way to enhance UX and achieve success in e-commerce.This research indicates that the Lean UX method can serve as a strong foundation in the process of redesigning a website to improve user experience. By emphasizing team collaboration and user involvement, UX enhancements can be effectively achieved, creating opportunities for business growth in a competitive digital environment.